Study Of Selection Of Delivery Assistance By Tbas In Materials In Masadian Village, Menui Sub-District, Menui Islands, Morowali District - Supriyadi Supriyadi; La Ode Liaumin Azim; Rasma Rasma; Mayurni Fardayana Malik; Saasa Saasa (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2023)
Backgroud: Nationally, indicators regarding the coverage of delivery services at health facilities have succeeded in achieving the objectives of the 2017 strategic plan, but in several provinces in Indonesia there are still significant differences regarding the coverage of delivery services, for example, Jakarta has the highest coverage at 102%, then Bali at 97.73 %. Meanwhile, Central Sulawesi Province only had an achievement of 76.18%. Objective: This study aims to find out the description of the selection of birth attendants by dukuns for mothers giving birth in Masadian Village, Menui District, Archipelago District, Morowali Regency. Method: This research has a type of quantitative design with a descriptive approach. The population in this study were all birth mothers assisted by traditional birth attendants in 2022, totaling 40 people. the sample in this study was a portion of mothers who were assisted by traditional birth attendants in 2020 as many as 29 respondents. The sampling technique in this study was purposive sampling. The research data was processed using descriptive statistical tests. Result: The results showed that 69% of the respondents had low education and 31% had higher education, 62.1% less knowledge of respondents and 37.9% good category, most of the respondents' economic status was 72.4% low economic and 27 high economic .6%, access to health services 100% access is not affordable, and husband/family support 51.7% do not receive family support and 48.3% receive family support. It is suggested to the puskesmas to provide education to the community which aims to increase the knowledge of mothers, husbands and other families so that they are ready and willing to give birth in midwivesKeywords: birth attendant, traditional birth attendant, knowledge, access, family support